Possible consequences of nutritional improvements for the economic development - Hans-Rimbert Hemmer (Intereconomics, 1979)
Studies of the relationship of nutrition and economic development have hitherto largely focused on the question how the state of nutrition has changed in consequence of economic developments. The analysis concentrated on the “passive role of nutrition”. In the following article the question is reversed: what possibilities exist for influencing the development process by measures of nutrition policy?
Keywords: 330; Nutrition